The Development of “Domi Kids” Android Based Application for Children - Karima Yustyalatifa; Ahmad Samawi; I Wayan Sutama; Munaisra Tri Tirtaningsih (UPI Kampus Cibiru, 2022)
The process of teaching religious values in early childhood can be done in various ways, such as an Android-based application. The use of android-based learning media makes the learning process more practical, effective, and efficient. Domi Kids application is designed to make it easier for children to learn to memorize daily prayers and short surah and assist parents in providing positive content during the child`s learning process using technology. The purpose of this research is to produce a mobile learning application product that contains daily prayers, short surah, and mini game to stimulate the ability of children ages 5-6 years to comprehend language, specifically memorizing daily prayers and short surah that are effective, efficient, and attractive. This study uses development research, which uses a simplified development model from ADDIE which includes: 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. The results showed that the Domi Kids application obtained a score of 97.02%, which means that the validation results are included in the very valid and usable level of validity.